Sex Differences in Brain of Migraineurs - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers at Children's Hospital Boston and other Harvard Medical School centers studied alterations in brain structure in male and female age-matched interictal (migraine free) migraineurs and controls, using high-field MRI.